Physicochemical and antioxidant properties of bovine caseinate hydrolysates obtained through microbial protease treatment - Hidalgo, María Eugenia (2012)
Q2 según Scimago At present, it is possible to obtain bioactive nutritional components through enzyme hydrolysis  under well-controlled and moderate conditions of pH and temperature. In this work we aimed for the production and characterization of bovine sodium caseinate (NaCAS) hydrolysates by  means of an extracellular protease from Bacillus sp. P45. Antioxidant properties were evaluated  through DPPH and TBARS assays. A glucono-δ-lactone acid-induced aggregation and gelation processes of the hydrolysates and their corresponding mixtures with NaCAS was also analyzed. Hereby, we demonstrate that the presence of hydrolysates affects the kinetic of NaCAS  aggregation processes but does not significantly alters the final state of the acid aggregates obtained.